Advances and Prospects in Biomaterials for Intervertebral Disk Regeneration - Li, Chunxu; Bai, Qiushi; Lai, Yuxiao; Tian, Jingjing; Li, Jiahao; Sun, Xiaodan; Zhao, Yu (Frontiers in Bioengineering and Biotechnology, 2021)
Low-back and neck-shoulder pains caused by intervertebral disk degeneration are highly prevalent among middle-aged and elderly people globally. The main therapy method for intervertebral disk degeneration is surgical intervention, including interbody fusion, disk replacement, and diskectomy. However, the stress changes caused by traditional fusion surgery are prone to degeneration of adjacent segments, while non-fusion surgery has problems, such as ossification of artificial intervertebral disks. To overcome these drawbacks, biomaterials that could endogenously regenerate the intervertebral disk and restore the biomechanical function of the intervertebral disk is imperative. Intervertebral disk is a fibrocartilaginous tissue, primarily comprising nucleus pulposus and annulus fibrosus. Nucleus pulposus (NP) contains high water and proteoglycan, and its main function is absorbing compressive forces and dispersing loads from physical activities to other body parts. Annulus fibrosus (AF) is a multilamellar structure that encloses the NP, comprises water and collagen, and supports compressive and shear stress during complex motion. Therefore, different biomaterials and tissue engineering strategies are required for the functional recovery of NP and AF based on their structures and function. Recently, great progress has been achieved on biomaterials for NP and AF made of functional polymers, such as chitosan, collagen, polylactic acid, and polycaprolactone. However, scaffolds regenerating intervertebral disk remain unexplored. Hence, several tissue engineering strategies based on cell transplantation and growth factors have been extensively researched. In this review, we summarized the functional polymers and tissue engineering strategies of NP and AF to endogenously regenerate degenerative intervertebral disk. The perspective and challenges of tissue engineering strategies using functional polymers, cell transplantation, and growth factor for generating degenerative intervertebral disks were also discussed.